If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying t = (x + -7)(2 + y) Reorder the terms: t = (-7 + x)(2 + y) Multiply (-7 + x) * (2 + y) t = (-7(2 + y) + x(2 + y)) t = ((2 * -7 + y * -7) + x(2 + y)) t = ((-14 + -7y) + x(2 + y)) t = (-14 + -7y + (2 * x + y * x)) t = (-14 + -7y + (2x + xy)) Reorder the terms: t = (-14 + 2x + xy + -7y) t = (-14 + 2x + xy + -7y) Solving t = -14 + 2x + xy + -7y Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Simplifying t = -14 + 2x + xy + -7y
| 9m=6(a+4) | | -19=2+4(h+7) | | 754/1000000 | | 3x(2x-3)=27 | | 17j-6=14j+7 | | 18.24=-16t^2+24t+8 | | 3n-9=2n+13 | | 8-6n=-7+5(5n+3) | | 7i/8i | | -8x+y=50 | | x-12/5=-6 | | 7-(2-y)=-4 | | 18.24=-16t+24t+8 | | x+39-3x-40=949 | | 9*45=5(f-32) | | (n-12)*8=80 | | x+x+37+4x-40=819 | | 19-5x=7x+19 | | -3y-27=-6(y+6) | | t=(x+y)(2x-y) | | 5*(x-2)=2+2x+x+4 | | 0=5x^2+15 | | 7x-32+3x+12=180 | | -24x=7x-4 | | (n-8)*8=32 | | 10y+8x=210 | | (j+9)(5j+7)=0 | | x^2-15x+68=0 | | 9(2+r)-3(r-1)=33 | | x+2=-36 | | (n-19)*3=12 | | 12*45= |